Aflibercept for diabetic macular edema: a concise review - Haridoss, Sujithera; Sundaram, Soundaram Meenakshi; George, Melvin; Sriram, Damal Kandadai (International Journal of Basic & Clinical Pharmacology, 2017)
Diabetic retinopathy and diabetic macular edema are associated with loss of vision in patients with diabetes worldwide. The treatment requires a multidisciplinary interventional approach. Among the available management options for DME, laser photocoagulation has been the standard of care. Due to its slow progression and inability to reverse the vision loss, an alternative treatment is needed. The role of vascular endothelial growth factors (VEGF) and inflammatory mediators led to the development of anti-VEGF agents, that stimulates retinal vasculogenesis and angiogenesis. Intravitreal aflibercept is an anti-angiogenic soluble decoy receptor with trap technology employed by fusion of multiple endogeneous receptor component, approved for the treatment of DME. Clinical trials of aflibercept comparing it with laser photocoagulation and other anti-VEGF have shown reliable efficacy, providing significantly positive visual and anatomical results. However, treatment regimens with monthly clinical visits and injections, challenge the patients comfort, thereby requiring the need to identify better strategies to lower injection frequencies.